AKTIVITAS ANTIJAMUR KRIM EKSTRAK ETANOL DAUN JAMBU MONYET (Anacardium occidentale L.) DAN KULIT BATANG RAMBUTAN (Nephelium lappaceum) TERHADAP Candida albicans - Devi Nisa Hidayati; Ulya Felasufah; Amaliyah Ayu Nurfitriani; Mufrod Mufrod (Universitas Wahid Hasyim Semarang, 2017)
ABSTRACT Ethanol extract of Anacardium occidentale and rambutan bark (Nephelium lappaceum) proved to have antifungal activity agains Candida albicans. Efforts to improve comfort and ease of use then made in the form of cream formulation.The aim of study is to know the antifungal activity of cream with various concentration of Anacardium occidentaleleaf extract and rambutan bark againstCandida albicans. Extraction of ethanol extractAnacardium occidentale leaf (EAOL) and rambutan bark (ERB) used maceration method. Solvents used ethanol 70% and ethanol 96%, respectively. Formulation cream of EAOL and ERB was maked 3 formulation. Formulation cream EAOL with concentration of variations extract are FI (10,5%), FII (12,5%), FIII (14,5%). Formulation cream ERB with concentration of varions extract are FI (10%), FII (15%), FIII (20%). Antifungal activity was determined in the cream using agar diffusion method and zone of inhibitionwere analyzed using descriptive. The results showed that antifungal activity against Candida albicans of cream EAOL concentration 14,5% with zone of inhibition is 7,16 ± 0,28 mm and cream ERB concentration 20% with zone of inhibition is 9,5 ± 0,5 mm. Kata Kunci : Antifungal, Anacardium occidentale, Nephelium lappaceum, Formulation ofcream